The Valuations of the Near Polygon ${\Bbb G}_n$ - De Bruyn, Bart (The Electronic Journal of Combinatorics, 2009)
We show that every valuation of the near $2n$-gon ${\Bbb G}_n$, $n ≥ 2$, is induced by a unique classical valuation of the dual polar space $DH(2n-1,4)$ into which ${\Bbb G}_n$ is isometrically embeddable.